“Does My Teacher Believe I Can Improve?”: The Role of Meta-Lay Theories in ESL Learners’ Mindsets and Need Satisfaction - Lou, Nigel Mantou; Noels, Kimberly Ann (Frontiers in Psychology, 2020)
Supporting students’ growth mindsets (i.e., beliefs that ability can be improved) and basic psychological needs (i.e., needs for autonomy, competence, and relatedness) are important ways to sustain their motivation and resilience after challenging situations. We argue that others’ feedback may support or undermine mindsets and need satisfaction simultaneously through students’ meta-lay theories – that is, students’ perceptions of whether others (in this case their teacher) believe that ability can be improved or not. We conducted a randomized controlled experiment in which 180 university students who spoke English as their second language failed a difficult English test and received either feedback from a teacher that consoled their lack of ability, feedback that focused on improving ability, or no feedback. We found that compared to students receiving no feedback, students receiving ability-consoling feedback perceived that the teacher believed less in their potential and felt less competent, and students receiving improvement-oriented feedback perceived that the teacher believed more in their potential. Consequently, meta-lay theory (“the teacher believes I can change my ability”) predicted students’ endorsement of growth mindsets (“I believe I can improve”) and need satisfaction (sense of competence, relatedness, and autonomy). In turn, mindsets and need satisfaction jointly predicted language confidence and beliefs about mistakes. Only need satisfaction, however, predicted task avoidance and duration of task engagement. Meta-lay theories underlie the processes through which feedback supports or undermines students’ resilience after failure.